Public Health Policy in the Age of Climate Change: Developing Sustainable Healthcare Systems for Future Generations - Trisnawati Trisnawati; Chen Mei; Yang Xiang (Yayasan Adra Karima Hubbi, 2026)
Background. Public health systems worldwide are increasingly challenged by the accelerating impacts of climate change, including extreme weather events, shifting disease patterns, and growing health inequities. These challenges expose structural vulnerabilities in existing healthcare systems and highlight the urgent need for policy frameworks that integrate sustainability, resilience, and long-term population health considerations. Purpose. This study aims to examine how public health policy can be reoriented to support the development of sustainable healthcare systems capable of protecting future generations in the context of climate change. Method. The research employed a qualitative–analytical approach based on a systematic review of international policy documents, peer-reviewed journal articles, and reports from global health and environmental organizations published between 2015 and 2024. The analysis focused on policy strategies linking climate adaptation, health system strengthening, and sustainability principles. Results. The findings indicate that effective public health policies increasingly emphasize cross-sector collaboration, climate-resilient health infrastructure, low-carbon healthcare delivery, and preventive, community-based interventions. Countries that integrate environmental considerations into health governance demonstrate greater capacity to manage climate-related health risks and reduce long-term system costs. Conclusion. The study concludes that sustainable healthcare systems require transformative public health policies that move beyond short-term crisis responses toward integrated, forward-looking strategies. Embedding climate resilience and sustainability into public health policy is essential for safeguarding health equity and ensuring the viability of healthcare systems for future generations.